Enhancing students' competence in writing popular articles on user-generated content-based digital media - Junaedi, Fajar; Sudiwijaya, Erwan; Suherman, Ansar; Khairiyah, Rizqi Lailatul (Universitas Muhammadiyah Magelang, 2025)
This community service program aims to enhance students' competence in writing popular articles. The activities were conducted in the form of a writing workshop using the Indonesian language according to journalistic standards. The program focused on developing the ability to compose popular articles and practicing the submission of article drafts to digital mass media publishers, particularly those based on user-generated content. As a result of this program, students from Universitas Muhammadiyah Buton successfully published 20 articles in digital mass media. This competence improvement is expected to support the promotion and contribution of Universitas Muhammadiyah Buton to society.